Injuries in Australian school-level rugby union. Issue 21 (2nd November 2017) - Leung, Felix T.; Franettovich Smith, Melinda M.; Hides, Julie A.
ABSTRACT: There is a high incidence of injuries in rugby union due to the physical nature of the game. In youth rugby union, there are large variations in injury rates reported. Our study investigated the rates of injuries in school-level rugby union players in Australia using the consensus statement for rugby union injuries. Injury surveillance was conducted on 480 rugby players from 1 school in Queensland, Australia. Injury data were collected using paper-based injury recording forms during the 8-week rugby season using a "medical-attention" injury definition. In total, 76 players sustained one or more injuries, with a total of 80 injuries recorded. The overall injury rate was 31.8 injuries/1000 match player hours (95% CI, 25.4–39.4). Concussion had an incidence rate of 6.0/1000 match player hours (95% CI, 3.5–9.6). The incidence of upper limb and lower limb injuries were 9.1 and 9.9/1000 match player hours, respectively (95% CI, 5.9–13.5 and 6.6–14.5). The older age divisions had higher injury rates and most injuries occurred while tackling or being tackled. The injury rates observed in this sample of Australian school rugby union players provides direction for future studies to enable informed decisions relating to development of injury prevention programmes at this level of rugby.